Analisis sajian buku ajar fisika sma kelas X semester 1 terkait komponen pendekatan contextual teaching and learning (CTL) - Doni Zulfadli; Desnita Desnita; Festiyed Festiyed; Syafriani Syafriani (Universitas Negeri Padang, 2019)
One approach which is suitable for learning Physics is the contextual approach (CTL approach). To implement CTL approaches the textbook used must be able to facilitate CTL approach. Currently there are many textbooks in circulation with various writers. For this reason, it is necessary to find out whether the outstanding textbooks have been able to facilitate CTL approaches in learning. The solution to this problem is to analyze the extent to which textbooks facilitate the implementation of CTL approaches. This type of research is a descriptive study with a qualitative approach. The population in this study are all senior high school physics class X textbooks circulating in West Sumatra. The sampling technique used Purposive Sampling type. The sample in this study was the four most textbooks used in West Sumatra Senior High School based on survey results. Data collection techniques in this study is study of documentation. The instrument used for data collection was an analysis sheet containing 7 CTL components. Then the instrument translated into 39 indicators. Each indicator contains one instrument. Data in this study were analyzed using simple statistics. From the research results the best book in facilitating CTL approach is Mediatama’s book with a percentage of 68.94% and the lowest score meeting is the Tiga Serangkai’s book with a percentage of 62.07%. All Textbooks are suitable for use in physics learning using the CTL approach.